1998
DOI: 10.1590/s0103-84781998000300029
|View full text |Cite
|
Sign up to set email alerts
|

Fitase na alimentação de poedeiras

Abstract: Os grãos utilizados nas rações possuem grande parte do seu fósforo na forma fítica, sendo indisponível para a absorção pelos não-ruminantes. Para corrigir esta indisponibilidade, têm-se suplementado as aves com fosfatas inorgânicos. Esta prática onera o custo das rações e pode apresentar efeitos adversos no desempenho das poedeiras, além de provocar problemas ambientais. A inclusão da enzima fitase na ração de poedeiras é uma das maneiras de aumentar a disponibilidade do fósforo de origem vegetal e, conseqüent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Vegetables are generally attributed to low values of phytase activity; however, Mroz et al (1994) demonstrated that wheat phytase can improve phosphorus digestibility from 27 to 50%. Furthermore, Kornegay (1996) demonstrated that wheat phytase acts at a much lower pH limit than fungal phytase (Figure 2) and highlighted some advantages, such as greater substrate specificity and therefore a lower affinity constant (Km) of fungal phytase when compared with plant origin (Fireman and Fireman, 1998).…”
Section: Phytasementioning
confidence: 99%
“…Vegetables are generally attributed to low values of phytase activity; however, Mroz et al (1994) demonstrated that wheat phytase can improve phosphorus digestibility from 27 to 50%. Furthermore, Kornegay (1996) demonstrated that wheat phytase acts at a much lower pH limit than fungal phytase (Figure 2) and highlighted some advantages, such as greater substrate specificity and therefore a lower affinity constant (Km) of fungal phytase when compared with plant origin (Fireman and Fireman, 1998).…”
Section: Phytasementioning
confidence: 99%
“…Due to the low content of available phosphorus in plants and the low phytase activity in birds, diets must be supplemented with an inorganic phosphorus source. Nevertheless, similar to phytic phosphorus, a great proportion of inorganic phosphorus is excreted by birds (Fireman & Fireman, 1998). The use of inorganic phosphorus in diets has many disadvantages, as the increase of nutrition costs and, consequently, production costs.…”
Section: Introductionmentioning
confidence: 99%
“…Simplificando, há quatro razões principais para uso de enzimas na alimentação animal: naquele tempo, o custo da produção da enzima era um obstáculo para seu uso. A produção comercial de fitase é facilmente atingida com culturas microbianas, mas, para que se processe a enzima em escala comercial, é necessário que o microrganismo a produza extracelularmente (FIREMAN, 1998).…”
Section: Funções E Metabolismo Do Fósforounclassified
“…Uma das maneiras de se prevenir os efeitos ambientais provocados pelo excesso de P na excreta dos animais, com a vantagem de aumentar a disponibilidade do P de fontes vegetais, é o uso da enzima fitase, a qual já é produzida comercialmente a partir de fungos do gênero Aspergillus ssp. seus mutantes e recombinantes(FIREMAN;FIREMAN, 1998) Fireman (1998),. mio-inositol-hexaquisfosfato, quando complexado com cátions bivalentes como Ca, Mn, Mg, Fe, zinco (Zn), etc..., o que também os torna indisponíveis para o animal.…”
unclassified